Assembly of fully substituted triazolochromenes via a novel multicomponent reaction or mechanochemical synthesis - Vroemans, Robby (Beilstein J Org Chem, 2018)
A new metal-free one-pot three-component procedure towards fully substituted triazolochromenes has been developed, starting from commercially available materials. Salicylaldehydes and nitroalkenes were reacted under solvent-free conditions, followed by a 1,3-dipolar cycloaddition of the intermediate 3-nitro-2H-chromenes with organic azides in a one-pot two-step sequence. The triazolochromenes were formed with complete regioselectivity and new biologically relevant structures were synthesized via extension of the developed procedure and via postfunctionalization. The mechanochemical synthesis was carried out for several salicylaldehydes and gave a clear improvement in the yield of the corresponding triazolochromenes and consequently showed to be a viable alternative for solid salicylaldehydes.